2022
DOI: 10.3390/diagnostics12051132
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Hypertrophic Cardiomyopathy in Hungary: Analysis of 242 Patients with a Panel of 98 Genes

Abstract: Hypertrophic cardiomyopathy (HCM) is a primary disease of the myocardium most commonly caused by mutations in sarcomeric genes. We aimed to perform a nationwide large-scale genetic analysis of a previously unreported, representative HCM cohort in Hungary. A total of 242 consecutive HCM index patients (127 men, 44 ± 11 years) were studied with next generation sequencing using a custom-designed gene-panel comprising 98 cardiomyopathy-related genes. A total of 90 patients (37%) carried pathogenic/likely pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…All carriers of the p.Q1233* variant were from the Central (Moscow) District of Russia and of Slavic origin. The MYBPC3 p.Q1233* variant has also been found to be very common in some Eastern European countries, such as Belarus and Hungary [44], where its founder effect has been confirmed. In Western countries, the prevalence of the p.Q1233* variant is less than 1% [24,26,34].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…All carriers of the p.Q1233* variant were from the Central (Moscow) District of Russia and of Slavic origin. The MYBPC3 p.Q1233* variant has also been found to be very common in some Eastern European countries, such as Belarus and Hungary [44], where its founder effect has been confirmed. In Western countries, the prevalence of the p.Q1233* variant is less than 1% [24,26,34].…”
Section: Discussionmentioning
confidence: 93%
“…There were no homozygous or compound heterozygous patients with two truncating variants (Figure 1). Compared to patients with a single P/LP/VUS-LP variant (n = 70), patients with two rare variants (n = 10) had a significantly higher SCD risk score (5.9 [3.5-7.3] vs. 2.9 [1.9-4.0], p = 0.011), larger left atrium (52 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] vs. 43 [39][40][41][42][43][44][45][46][47][48][49][50] mm, p = 0.017), more frequent high systolic pulmonary artery pressure (63 vs. 14%, p = 0.004), and a trend toward more frequent severe NYHA class III/IV (38 vs. 11%, p = 0.07). The clinical course of HCM was highly variable, ranging from mild symptoms to severe HF progression and SCD in middle age.…”
Section: • Multiple Variantsmentioning
confidence: 99%
“…FHOD3 was only recently added to the list of intrinsic genes implicated in HCM in 2022 [2]. Therefore, it has not been included in earlier studies using panel sequencing to elucidate the genetic background of patients with HCM [29][30][31]. With the inclusion of the FHOD3 in cardiomyopathy gene panels, the prevalence of FHOD3-associated HCM could be significantly higher than currently estimated, particularly among patients with HCM with Balkan ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…No excess TTN variants were noted in cases compared to controls in two studies. 34,35 There is one report of a frameshift located in the A-band (percent spliced-in; PSI 100%), 36 and one termination in the I-band (PSI 100%) 37 in individuals with HCM. One study reported a missense variant in an immunoglobulin domain near the M-line A-band transition zone of TTN in a medaka mutagenesis fish model with diastolic dysfunction, highlighting this as an important region.…”
Section: Downgraded and Notable Gene Re-curationsmentioning
confidence: 99%